Assessment of Septoplasty Outcome using Nasal Obstruction Symptom Evaluation Scale - Shrestha, Kundan Kumar; Joshi, R.R.; Rijal, A.S.; Dhungana, A.; Maharjan, S. (Nepal Medical College Journal, 2019)
Nasal obstruction, the most common presenting symptom in nasal and sinus disease, is defined as patient discomfort manifested as a sensation of insufficient airflow through the nose. Nasal septal deviation is the most common anatomical cause of nasal obstruction. Surgical correction of a deviated septum, nasal septoplasty, is the definitive treatment for septal deviation. Many studies have discussed about outcomes of septoplasty. However, there is limited published literature on nasal septoplasty and its outcome in Nepal. The aim of this study is to evaluate the outcome of septoplasty using Nasal Obstruction Symptom Evaluation (NOSE) scale, a validated outcome instrument assessing quality of life (QoL) related to nasal obstruction. A total of 52 patients aged 18 years and above, with nasal obstruction at least for 3 months, undergoing septoplasty alone were included in the study. Baseline NOSE score was calculated a week before surgery. The patients were followed up after 3 months to record postoperative NOSE score. On statistical analysis, the mean NOSE scores before and 3 months after septoplasty were 45.58±21.38 and 8.46±8.37 respectively. The mean difference was 37.11± 21.22 and p value on paired t test was less than 0.001(highly significant). The mean differences of each component of the NOSE scale questionnaire were also found to be highly significant statistically with p values less than 0.001. Gender and age did not seem to affect the outcomes. In conclusion, NOSE scale is a valid, reliable and responsive instrument that is brief and easy to complete and has potential use for outcome studies in adults with nasal obstruction. This instrument showed that septoplasty, if done in properly selected patients, results in significant improvement in nasal obstruction and disease specific quality of life with high patient satisfaction.